Earliest evidence for invasive mitigation of dental caries by Neanderthals - Alisa V. Zubova; Lydia V. Zotkina; John W. Olsen; Alexander M. Kulkov; Vyacheslav G. Moiseyev; Anna A. Malyutina; Roman V. Davydov; Sergey V. Markin; Eugene A. Maksimovskiy; Pavel V. Chistyakov; Andrey I. Krivoshapkin; Ksenia A. Kolobova (PLoS ONE, 2026)
Neanderthal medical knowledge has long attracted scholarly interest. Evidence suggests they cared for sick, injured, and elderly group members, with possible use of medicinal plants. However, it remains uncertain whether such practices reflect deliberate medical strategies or instinctive self-medication akin to that observed in non-human primates. Here, we analyze and interpret traces of deliberate artificial manipulation of Chagyrskaya 64, a Neanderthal lower left second molar found in Chagyrskaya Cave (Altai Krai, Russia). The tooth exhibits a large human-generated concavity on the occlusal surface, created during the lifetime of the individual. Traceological and microtomographic analyses of the observed modifications, combined with experimental verification, reveal that the concavity in Chagyrskaya 64 is indicative of the earliest documented instance of caries treatment involving the drilling/rotating with a lithic perforator, ca. 59 ka. Evidence of two distinct types of manipulations requiring different tools, in addition to the drilling/rotating technique, necessitating complex finger movements, indicates that the Chagyrskaya Cave Neanderthals possessed the cognitive capacity to intuit the source of pain, comprehend the feasibility of its elimination, and deliberately select the most efficacious dental intervention. These patterns bring Neanderthal behavior closer to modern humans and differentiate that behavior from the instinctive actions of other primates.